Essays on the Behavior of Firms and Politicians - Marina Riem (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2017)
This dissertation consists of six self-contained chapters that are related to the behavior of firms and politicians in a broader sense. After an introduction to the topic, the first part of the dissertation elaborates on how institutional and political framework conditions influence the behavior of firms. Chapter 2 examines the determinants of inter vivos transfers of ownership in German family firms. Survey evidence indicates that owners of larger firms, and firms with strong current business conditions, transfer ownership at higher rates than others. Chapter 3 investigates how political uncertainty influences corporate investment decisions employing data on firms' self-reported investment realizations, plans and revisions. The results show that realized investment ratios decreased in years when state elections occurred relative to the average investment ratio in years with no state election. Firms however seem to anticipate electoral uncertainty already when making investment plans and hardly revise their plans. Chapter 4 examines whether political uncertainty influences how firm owners perceive their present state and future development of business. The results show that firm owners expect their business to develop better before state elections and worse after state elections. The second part of this dissertation investigates how partisanship and self-interest of politicians shape their ethos and behavior. Chapter 5 describes how partisanship shapes the attitudes and actions of politicians in Germany. The results show that German state politicians' and governments' words differed from actions regarding budget consolidation and the German debt brake. Chapter 6 examines whether parties punish politicians who vote against the party line in roll-call votes. The results do not show that parties account for the voting behavior by punishing politicians who have voted against the party line.
Keywords: C23; D22; D24; D31; D72; D81; D92; H24; H25; H32; H60; H70; H72; H73; I23; 330; Inter vivos transfers; transfer taxes; family firms; firm-level investment; user cost of capital; political uncertainty; elections; survey data; panel data; business perceptions; government ideology; public debt; debt brake; balanced-budget rule; constitution; expressive rhetoric; voting against the party line; adherence to the party line; roll-call votes; proportional representation; party lists; selectorate; decision making in committees; minority voting; policy preferences; Joint Economic Forecast of German economic research institutes.